Faculty learning communities : Communities of practice that support, inspire, engage and transform higher education classrooms - Rainville, Kristin N.; Desrochers, Cynthia G.; Title, David G. (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"This edited book on Faculty Learning Communities (FLCs) provides and explores powerful examples of FLCs as a impactful form of professional learning for faculty in higher education. The chapters describe faculty learning community initiatives across different fields of study and within dynamic and flexible teaching and learning models. Contributing authors provide a framework for faculty learning communities, show the impact of faculty learning communities on teaching practices or student learning, and describe how these communities of practice can lead to institutional change. The book's foreword, by Milton D. Cox, investigates the changes in the FLC world over the past decade: the influence of Communities of Practices (CoP), recent recommendations about virtual FLCs and CoPs, and the positive affirmation for FLCs that implementation science has provided"-- Provided by publisher.
Keywords: Professional learning communities.; Communities of practice.; College teachers -- Professional relationships.; Education, Higher -- Aims and objectives.; Education -- Professional Development.; Teacher training.; elektronické knihy; electronic books